Pre-clinical efficacy evaluation of human umbilical cord mesenchymal stem cells for ischemic stroke - Shen, Danpeng; Wang, Hongwei; Zhu, Hongyan; Jiang, Cuibao; Xie, Fan; Zhang, Hongpeng; Lv, Qian; Liu, Qi; Wang, Zhiqiang; Qi, Nianmin; Wang, Hao (Frontiers in Immunology, 2023)
Objective This study explored the underlying therapeutic mechanism of human umbilical cord mesenchymal stem cells (hUCMSCs) for ischemic stroke (IS), and determined the optimal administration time windows and dose-effect relationship. Methods The levels of SDF-1α, IL-10, IL-6, TNF-α, BDNF, IL-1β, and VEGF-A factors in serum and brain tissue lysate were measured by ELISA. The pathological status of brain tissues was evaluated by Hematoxylin-Eosin (HE) staining, and apoptosis of nerve cells was detected by tunel. The protein expression of CXCR-4, NeuN, and Nestin in the brain tissues was assessed through immunofluorescence. The balance beam, forelimb muscle strength, and limb placement were tested on MCAO rats at different time points and doses. The infarct area of the rat brain tissues was measured at the end of the experiment. Results The hUCMSC treatment during the acute phase of MCAO significantly reduced the secretion of IL-6, TNF-α, IL-1β but increased IL-10 in serum, and the levels of SDF-α and BDNF in serum and brain tissues lysate were also increased. The pathological results showed that there were more neurons in the treatment group compared to the model group. Immunofluorescence assays showed that the expression of CXCR4、Nestin、NeuN was relatively higher than that in the model group. The d4 and d7 treatment significantly improves the motor function, promotes the recovery of forelimb muscle strength, increases the forelimb placement rate and reduces the scope of cerebral infarction, but the d14 treatment group has less therapeutic effect compared to the d4 and d7 treatment. The 2×107/kg treatment showed the best therapeutic effect, followed by the 1×107/kg treatment, and the worst is 0.5×107/kg treatment from the test of balance beam, forelimb muscle strength, limb placement and the infarct area of the rat brain tissues. Conclusion The hUCMSCs can inhibit the infiltration of inflammatory cells in the brain tissue, and promote the repair of brain tissue structure and function. Early intervention by injecting high-dose of hUCMSCs can significantly improve the recovery of neurological/motor function and reduce the size of cerebral infarction in rats.